2013
DOI: 10.1016/j.jtbi.2013.02.007
|View full text |Cite
|
Sign up to set email alerts
|

A lifelong model for the female reproductive cycle with an antimüllerian hormone treatment to delay menopause

Abstract: A system of 16 non-linear, delay differential equations with 66 parameters is developed to model hormonal regulation of the menstrual cycle of a woman from age 20 to 51. This mechanistic model predicts changes in follicle numbers and reproductive hormones that naturally occur over that time span. In particular, the model illustrates the decline in the pool of primordial follicles from age 20 to menopause as reported in the biological literature. Also, model simulations exhibit a decrease in antimüllerian hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Alternatively, the collapse of the primordial follicle population may be indirect and subsequent to the profound effects on the developing follicle population. However, the possibility that prolonged elevation in AMH is toxic to dormant primordial follicles requires urgent investigation because AMH treatment has been proposed as a reversible contraceptive and a therapeutic inhibitor of ovarian reserve depletion (Margolskee & Selgrade 2013, Hayes et al 2016, Kong et al 2016, Kano et al 2017. The loss of primordial follicles is thought to be irreversible and the 5-month-old Thy1.2-AMH Tg phenotype indicates that more research is needed to determine the safety of longterm AMH treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the collapse of the primordial follicle population may be indirect and subsequent to the profound effects on the developing follicle population. However, the possibility that prolonged elevation in AMH is toxic to dormant primordial follicles requires urgent investigation because AMH treatment has been proposed as a reversible contraceptive and a therapeutic inhibitor of ovarian reserve depletion (Margolskee & Selgrade 2013, Hayes et al 2016, Kong et al 2016, Kano et al 2017. The loss of primordial follicles is thought to be irreversible and the 5-month-old Thy1.2-AMH Tg phenotype indicates that more research is needed to determine the safety of longterm AMH treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Welt et al [50] collected data for two types of inhibin, InhA and InhB. Both inhibit FSH synthesis but InhB is a good indicator of ovarian aging and is useful for extending the model to older reproductive women in the age range 35-45 years (see [23]). Another refinement would be to separate the functions of the pituitary and hypothalamus in order to describe the role of gonadotropin releasing hormone (GnRH), because many cycle abnormalities involve irregular GnRH pulsing.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Over the last 10-15 years, we have developed and analyzed mechanistic, deterministic, mathematical models [14,15,17,23,32,39,[41][42][43][44] which predict average serum concentrations of reproductive hormones that agree with data in the biological literature for normally cycling adult women [27,50]. This article reviews the procedure which we and other modelers, e.g., Boer et al [3], Bogumil et al [4,5], Chen and Ward [7], Reinecke and Deuflhard [34], Röblitz et al [35], and Zeeman et al [55], have found effective for modeling hormonal regulation of the female reproductive system.…”
Section: Introductionmentioning
confidence: 99%
“…The model can be refined by embedding additional variables to include more detailed biological knowledge. In particular, the distinction between two types of inhibin (inhibin A and inhibin B), which affect differentially the synthesis of FSH, and the role of Anti-Müllerian Hormone (AMH) on the developing follicles was included in [25]. These refinements allowed the authors to broaden the timescale of the model up to a lifelong model, and to investigate the impact of a putative AMH treatment on the onset of menopause.…”
Section: 1) Modeling the Fluctuations In Hormonal Levels As The Resmentioning
confidence: 99%